(untitled) (International Journal of Food and Nutritional Sciences, 2021)
The purpose of this study is to find out the attitude level of Misings women towards women education. The study will be conducted in PaniMiri village of west Dibrugarh district, Assam state. The study will be carried out to find out the attitude level of Misings women towards women education. The data collected will be analyzed using simple percentage. This purpose of this paper is to know the mindset of the Misings women towards education in relation to socio-economic statuses so that adequate measures can be provided to them and help the society in the development process.